Strong convergence of a modified implicit iteration process for a finite family of Z-operators - Arif Rafiq (International Journal of Mathematics and Mathematical Sciences)
The purpose of this note is to establish a strong convergence of a modified implicit iteration process to a common fixed point for a finite family of Z-operators.